The Genus Phyllanthus: An Ethnopharmacological, Phytochemical, and Pharmacological Review. (20th April 2016) - Mao, Xin; Wu, Ling-Fang; Guo, Hong-Ling; Chen, Wen-Jing; Cui, Ya-Ping; Qi, Qi; Li, Shi; Liang, Wen-Yi; Yang, Guang-Hui; Shao, Yan-Yan; Zhu, Dan; She, Gai-Mei; et al.
Abstract : The plants of the genus Phyllanthus (Euphorbiaceae) have been used as traditional medicinal materials for a long time in China, India, Brazil, and the Southeast Asian countries. They can be used for the treatment of digestive disease, jaundice, and renal calculus. This review discusses the ethnopharmacological, phytochemical, and pharmacological studies of Phyllanthus over the past few decades. More than 510 compounds have been isolated, the majority of which are lignins, triterpenoids, flavonoids, and tannins. The researches of their remarkable antiviral, antioxidant, antidiabetic, and anticancer activities have become hot topics. More pharmacological screenings and phytochemical investigations are required to support the traditional uses and develop leading compounds.